The Rise of Open Banking: A Comprehensive Analysis of Research Trends and Collaborative Networks - V., Shacheendran; Lukose, Alan; John, Josiah; Joseph, Dawn; Joseph, Jeena (International Journal of Economics and Financial Issues, 2024)
This study explores the changing landscape of Open Banking-a financial services model where third-party providers get access through APIs to banking data for further innovation and customer experience improvements. The analysis is based on Scopus bibliographic data and relies on Biblioshiny and Citespace for the analysis of trends from 1999 to 2024. The main indicators analyzed include the dynamics of the annual scientific production, which increased after 2018 by a factor driven by regulatory frameworks such as PSD2. The main contributors are leading authors and sources, among them the Journal of Payments Strategy and Systems, while country-specific analyses definitely point out the UK, India, and China as major Open Banking research hubs. Thematic and trend analyses show that themes like data sharing, fintech, and API regulation are well-developed, whereas API security and risk management are still underexplored. Co-citation network visualizations depicted clear collaboration networks between countries and then between key authors. Factorial analysis further identified clusters of research related to technologically integrated themes, such as machine learning and blockchain. Key research gaps were identified in areas such as security and risk management, which are considered critical, with Open Banking’s continued expansion across the world. Practical implications include more robust API security frameworks and a deeper dive into the advanced technology-regulatory compliance link.